Pendidikan dan Penyuluhan Mengenai Kesehatan Gigi dan Mulut pada Komunitas Cinta Berkain Indonesia di Masa Pandemi Covid-19 - Tiarma Talenta Theresia; Raden Roro Asyurati Asia; Dewi Priandini; Arianne Dwimega; Jackson (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
The Covid-19 pandemic that has occurred since the beginning of 2020 has had a social and economic impact on people's lives. The government is trying to stop the spread of the coronavirus by pursuing a Pembatasan Sosial Berskala Besar (PSBB) and Adaptasi Kebiasaan Baru (AKB) Several communities are reported to have indications of the spread of the disease, including sports, worship, and hobby communities. This is because, among other things, the spread of Covid-19 is very easy to happens when there are crowds of people who don't pay attention to personal hygiene. Therefore, it is necessary to conduct counseling and training on dental and oral health for the Komunitas Cinta Berkain Indonesia during the adaptation of new habits to prevent the transmission of COVID-19. The training and counseling were conducted online using presentations on how to maintain oral health in the Indonesian cloth-loving community. Training and counseling were carried out for 20 community cadres for 60 minutes. Participants' knowledge was assessed by pre-test and post-test using Google Forms. From the results obtained, it was seen that there was an increase in the knowledge of the extension participants by 10% (the mean pre-test value was 70.26Â±9.05 and the post-test average was 77.1Â±6.08).